The Great Melding : War, the Dixiecrat Rebellion, and the Southern Model for America's New Conservatism - Feldman, Glenn (Book collections on Project MUSE., 2015)
One in which the New Deal consensus shattered and the Democratic and Republican parties fought off a third-party revolt only to find themselves irrevocably altered by their success. The Great Melding will fascinate historians, political scientists, political strategists, and readers of political nonfiction.